Artificial Intelligence in Agricultural Extension for Sustainable Development - Ibrahim, Umar (MultiTech Publisher, 2023)
The intersection of Artificial Intelligence (AI) and Agricultural Extension holds immense potential for enhancing sustainable development in the agricultural sector. This paper explores the transformative role of AI in agricultural extension services and its implications for sustainable development. Through a comprehensive literature review, data analysis, and case studies, we assess the current state of AI applications in agriculture and highlight the gaps and challenges in this field. Our study reveals that AI technologies offer innovative solutions for knowledge dissemination, decision support, and resource management in agriculture, contributing to increased yields, reduced environmental impact, and improved livelihoods for farmers. However, challenges related to data quality, accessibility, and ethical considerations need to be addressed. The paper also discusses the policy implications of integrating AI into agricultural extension programs and suggests future research directions. In conclusion, this research underscores the critical role of AI in agricultural extension for sustainable development, emphasizing its potential to revolutionize the agricultural landscape.